2021
DOI: 10.1016/j.meegid.2021.105098
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D receptor gene polymorphisms and clinical/severe outcomes of COVID-19 patients

Abstract: Introduction Growing evidence documented the critical impacts of vitamin D (VD) in the prognosis of COVID-19 patients. The functions of VD are dependent on the vitamin D receptor (VDR) in the VD/VDR signaling pathway. Therefore, we aimed to assess the association of VDR gene polymorphisms with COVID-19 outcomes. Methods In the present study, eight VDR single nucleotide polymorphisms (SNPs) were genotyped by polymerase chain reaction-restriction fragment length polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 98 publications
(86 reference statements)
0
38
2
Order By: Relevance
“…Bsm I was not related to disease severity in our study, but Abdollahzadeh et al 42 reported that the b allele was found to be a predisposition factor to COVID-19 severity.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Bsm I was not related to disease severity in our study, but Abdollahzadeh et al 42 reported that the b allele was found to be a predisposition factor to COVID-19 severity.…”
Section: Discussioncontrasting
confidence: 80%
“…In short, the f allele has affected the prognosis of subjects, and the FF genotype was mainly detected in subjects with a good prognosis, which can be a protective factor against ICU admission. In Abdollahzadeh et al's study, 42 Fok I f allele was also positively associated with signs, symptoms, and the severity of COVID‐19 affected people.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is a powerful modulator of the immune system [ 141 ], with antimicrobial functions [ 139 , 142 ]. VD exerts its functions through interaction with a nuclear vitamin D receptor (VDR) [ 143 ], in the VD/VDR signaling pathway [ 144 ]. This receptor is expressed in a wide variety of immune cells, influencing the secretion of cytokines and the function of different populations of lymphocytes [ 139 , 145 ].…”
Section: Interaction Covid-19 and Multiple Sclerosismentioning
confidence: 99%